An uncommon presentation of a large vulval wart in a child. (February 2022) - Lodhia, Jay; Mremi, Alex; Mbwambo, Orgeness Jasper; Mshangama, Seif; Bright, Frank; Ngowi, Bartholomeo Nicholaus
Abstract: Introduction and importance: Ano-genital warts are rare presentation in children. The main route of transmission is by sexual intercourse however horizontal transmission, self-inoculation and vertical transmission are also documented. Establishing the route of transmission when there is no evidence of sexual abuse may be difficult in pediatric and female virgins such as in our case report. Surgical excision remains one of the best options for treatment of large warts in pediatrics. To the best of our knowledge, this is the first report of novel case of large genital warts in pediatrics in Tanzania. Case presentation: We present a case of female child of one year and 10 months old with large ano-genital cauli-flower masses admitted at Kilimanjaro Christian Medical Centre. The child's hymen was intact and with no evidence of sexual abuse identified. The masses were excised under general anesthesia and histology confirmed Condyloma acuminata . Clinical discussion: Ano-genital warts are rare presentation in pediatrics and female virgins. Sexual abuse should be ruled out in pediatrics patients. Self-inoculation is described as a possible route of transmission in pediatrics and in female virgins. Horizontal and vertical transmissions are also possible route of transmission of HPV. It might be difficult to establish the route of transmission as in our case report. The warts were successful treated by surgical excision and cauterization. Conclusion: Condyloma acuminata are rare in pediatrics and establishing the route of transmission may be difficult. Sexual abuse should be ruled out in pediatrics. Highlights: Large genital warts are uncommon to the pediatric population. If encountered in children, sexual assault/abuse should be ruled out. The exact route of transmission in pediatrics without sexual abuse and female virgins may be difficult to establish. HPV can be transmitted through horizontal and self-inoculation. Surgical excision and electro-cauterization are effective treatment for pediatric genital warts